2014
DOI: 10.3389/fphys.2014.00170
|View full text |Cite|
|
Sign up to set email alerts
|

G-CSF does not influence C2C12 myogenesis despite receptor expression in healthy and dystrophic skeletal muscle

Abstract: Granulocyte-colony stimulating factor (G-CSF) increases recovery of rodent skeletal muscles after injury, and increases muscle function in rodent models of neuromuscular disease. However, the mechanisms by which G-CSF mediates these effects are poorly understood. G-CSF acts by binding to the membrane spanning G-CSFR and activating multiple intracellular signaling pathways. Expression of the G-CSFR within the haematopoietic system is well known, but more recently it has been demonstrated to be expressed in othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 54 publications
5
25
0
Order By: Relevance
“…They also observed a stimulatory effect of G-CSF on the proliferation of healthy C2C12 in vitro and evidence was presented in support of G-CSF as a direct activator of various signaling pathways related to cell proliferation, including PI3K/Akt and MAPK signals. Wright et al [15], on the other hand, found that CSF3R is expressed not only in active myoblasts, but also in myotubes and in mature SKM tissues. They found no evidence that G-CSF would influence in vitro proliferation of healthy C2C12 myoblasts and, in fact, it did not activate the above-mentioned signaling pathways either.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…They also observed a stimulatory effect of G-CSF on the proliferation of healthy C2C12 in vitro and evidence was presented in support of G-CSF as a direct activator of various signaling pathways related to cell proliferation, including PI3K/Akt and MAPK signals. Wright et al [15], on the other hand, found that CSF3R is expressed not only in active myoblasts, but also in myotubes and in mature SKM tissues. They found no evidence that G-CSF would influence in vitro proliferation of healthy C2C12 myoblasts and, in fact, it did not activate the above-mentioned signaling pathways either.…”
Section: Discussionmentioning
confidence: 99%
“…CSF3R is expressed in regenerating myocytes [11] and enhances proliferation of satellite cells in vivo [11,47]. Administration of G-CSF facilitates the regeneration of cardiotoxin-injured SKM [48] and protects against muscle degeneration in MDX mice [16]. Some progress has also been made in order to investigate whether the effects of G-CSF on muscle cells can be observed in vitro where myoblasts are deprived of their natural niche.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations